BREASTFEEDING FOR LOW-WEIGHT NEW-BORNS FOLLOWING DISCHARGE FROM HOSPITAL - Elaine Lutz Martins; Stela Maris de Mello Padoin; Andressa Peripolli Rodrigues; Samuel Spiegelberg Zuge; Cristiane Cardoso de Paula; Tatiane Correa Trojahn (Universidade Federal do Paraná, 2013)
This study aimed to describe the relation between breastfeeding for low-weight new-borns following discharge from the Neonatal Intensive Care Unit with socio-demographic and clinical characteristics. This quantitative and cross-sectional research was undertaken in 2011 with a population of 66 low-weight new-borns. Based on the bi-variate analysis, the factors related to breastfeeding were: a married mother, aged between 21 and 25 years old, with high school complete, and an income of one to three minimum salaries, to have undertaken more than six pre-natal consultations, to be multiparous and to have had a caesarean birth; a new-born with low weight at birth and a weight of 1.901 to 2.200 grams on discharge from the unit. To support breastfeeding it is necessary to offer help with the initiation of sucking and maintenance of lactation, taking into account the socio-demographic and clinical characteristics which can influence this process.